An Institutional Field of People Living with HIV/AIDS Organizations in Tanzania: Agency, Culture, Dialogue, and Structure - Olufowote, James Olumide (Frontiers in Communication, 2017)
Communication research on public health organizations and people living with HIV/AIDS (PLWHA) have paid insufficient attention to PLWHA organizations. These organizations, constituted and operated by PLWHA, advocate on behalf of PLWHA with more powerful institutions in society and serve as sources of empowerment and support. I drew on the culture-centered approach to health communication and institutional perspectives on health organizations to explore PLWHA organizations in Tanzania, namely their cultural and structural contexts, agency, and dialogue. Tanzania has 1.5 million PLWHA and a 5.3% adult prevalence rate that ranks it as 12th highest in the world. Through interviews with leaders of 10 PLWHA organizations, I found a cultural context of HIV stigma and discrimination, a structural context consisting of both corruption and bureaucratic politics in governing bodies as well as lack of access to resources, agency to impact PLWHA and members of society in a variety of ways, and processes of dialogue within advocacy networks of PLWHA organizations and in network collaborations with the government. I conclude with implications for improving the organizations’ interactions with their structural context and for developing the contribution from the culture-centered approach to health communication on structures-as-health-organizations-and-systems.